Penerapan Bueger Allen Exercise terhadap Nilai Ankle Bracial Index (ABI) dalam Upaya Peningkatan Perfusi Perifer Tidak Efektif pada Penderita Diabetes Melitus Tipe 2 - Mulya, Fatwa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Diabetes mellitus is a chronic metabolic and inflammatory disease accompanied by insulin resistance, hyperglycemia, and impaired insulin secretion from the pancreas. The most common complaint is tingling or numbness in the feet. Signs of tingling and numbness along with burning pain or swelling also appear which are signs that the nerves are being damaged by diabetes. One of the non-pharmacological techniques is the Bueger Allen Exercise. Buerger Allen Exercise is a varied movement exercise on the lower legs by utilizing gravity which is carried out gradually and regularly. The method used is pre-test and post-test. The implementation time is carried out for 6 days with 6 applications, namely in April 2025. The implementation time of the Bueger Allen Exercise is 1 time a day for 15 minutes. The place of implementation is in Sungai Putih Tapung Village. The results of the study showed an increase in ABI values ​​before and after BAE (Bueger Allen Exercise) was carried out.